Housing Market and Agglomeration of Rent-Seeking Activities: Implications for Regional Development - Shin-Kun Peng (European Regional Science Association (ERSA), 2014)
Rent-seeking is defined as exercising privileges or expending resources in order to obtain uncompensated gain by redistributing the wealth of others without reciprocating any benefits back to society through wealth creation. This paper pioneers in analyzing the agglomeration of rent-seeking activities in geography and the corresponding impact on regional economies. First of all, we construct a theoretical model based on the standard settings in the literature of economic geography with two types of mobile workers. Each agent maximizes his/her utility, whereas the distribution of agents' type corresponds to a map of productive and rent-seeking activities. Next, conditions for the agglomeration of rent-seeking activities are characterized, which constitute partially segregated equilibria. Finally, based on a panel data analysis for the conterminous 48 states in the U.S., we examine by how much the regional per capita real GDP drops when there is an extra 1 percent increase in the rent-seeking activities in the housing market.
Keywords: D50; D72; O18; 330